2001
DOI: 10.1192/bjp.178.5.458
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of suicide rates to social factors and availability of lethal methods

Abstract: Reduced exposure to lethal methods was responsible for the fall in rate in both genders, while the gender difference in favour of women may be related to their preference for non-violent methods or to their being less affected by the social changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 15 publications
1
32
0
3
Order By: Relevance
“…With the exception of firearms suicides, which form a very small proportion of suicides here, hanging is the most lethal suicide method recorded and international research has suggested that males are more likely to be attracted to the more lethal and violent suicide methods than females. 2,4,[6][7][8][9][10][11][12] Echoes of this are found in the suicide trends here. The most common suicide method among females in Ireland is poisoning, generally accepted to be a less lethal approach than hanging, which is the most common method among males.…”
Section: Table 1 About Herementioning
confidence: 75%
See 1 more Smart Citation
“…With the exception of firearms suicides, which form a very small proportion of suicides here, hanging is the most lethal suicide method recorded and international research has suggested that males are more likely to be attracted to the more lethal and violent suicide methods than females. 2,4,[6][7][8][9][10][11][12] Echoes of this are found in the suicide trends here. The most common suicide method among females in Ireland is poisoning, generally accepted to be a less lethal approach than hanging, which is the most common method among males.…”
Section: Table 1 About Herementioning
confidence: 75%
“…Past research has reported that being single or divorced is a risk factor for suicide, 6,13 and that marriage is a protective factor.…”
Section: Table 1 About Herementioning
confidence: 99%
“…Inclusion of this variable was an exploratory endeavour. Past research suggested that being single is a risk factor for suicide, 33,34 but there is contradictory findings in relation to firearms suicides. 8,10,16,19,35 In drawing this together into some form of coherent explanation of the sociodemographic differences across the FAS and n-FAS groups, it would appear that availability and socio-cultural acceptability are at the root of these findings.…”
Section: Betweenmentioning
confidence: 97%
“…Caraveo 5 encontró que las mujeres presentan mayor comorbilidad y depresión; Medina-Mora 3 reportó que la depresión mayor y la neurosis predominan en mujeres; Rascón 4 encontró que la depresión mayor, la depresión neurótica y el trastorno obsesivo-compulsivo fueron más frecuentes en mujeres (19,5% mujeres y 14,3% hombres); un análisis regional de América reportó más psicosis afectivas en mujeres 13 ; además presentan mayor hospitalización por intento suicida 14 . Por otra parte, los trastornos más severos son más frecuentes en varones; predominando los relacionados con el alcohol 15 y drogas ilegales 13,16,17 ; en Suecia se encontraron tasas más altas en varones de esquizofrenia y abuso de sustancias, mientras que las neurosis fueron más frecuentes en mujeres 18 ; en el Reino Unido (1961-1965 y 1985-1994) se observó una disminución general de suicidio, pero el descenso fue menor en varones, esta diferencia se relacionó con el mayor uso de métodos menos violentos en mujeres 19 , hecho que hay que ponderar con la mayor frecuencia de suicidio en varones por el uso de métodos más letales 14 . Sobre la relación entre género y trabajo se ha encontrado que taquilleras de la Cd.…”
Section: Introductionunclassified